An Investigation of dendrite formation in electroless copper thin film conductors - Olmos, Edwin Lasig (2007)
An investigation on the formation of dendrites across electroless copper thin film conductors was conducted using the water drop test approach. Aqueous solutions of NaCl, KCl, and CaCl2 at 1.0x10-4M and 5.0x10-4M, as well as mixtures of NaCl and KCl solutions were prepared and used as drop solutions. Results of different 23 factorial design of experiments showed that the voltage gradient, contaminant concentration, contaminant cation radius, cation valence as well as some two-factor interactions had significant effects on the time-to-short of copper dendrites. SEM micrographs of the dendrites were obtained for surface morphological analysis. An induction period of at least 3 seconds was observed prior to the appearance of the copper dendrite on the cathode surface, while a current level of at least 20uA at the time-to-short was recorded in all of the water drop tests. Preheating the test samples on a hot plate for 1 -3 minutes at 160- 190°C in the presence of air prior to the water drop tests showed some hindering effects on the induction periods and affected the time-to-short values. The average number of dendrites (length > 0.075mm) at the time-to-short decreased linearly when the voltage gradient was increased from 8 to 16v/mm. On the other hand, the average dendrite growth rate increased almost linearly when the voltage gradient was increased from 8 to 16v/mm. Comparison of the plot for the time-to-short vs. voltage gradient with the plot for the induction period vs. voltage gradient showed similar trends. The plots of the dendrite length against time, which showed a sharp linear increase at high voltage gradients of 12 and 16v/mm, and a gradual two-step increase at a low voltage gradient of 8v/mm, imply that nucleation and growth processes are involved in dendrite formation. An estimate of the diffusion layer thickness was made using the Nernst boundary layer equation. Extending the water drop tests to beyond the time-to-short showed that the subsequent dendrite growth patterns were more dense, more vertically oriented, and relatively thinner when using a higher voltage gradient of 16v/mm than at a lower voltage gradient of 8v/mm. Possible copper dendrite growth mechanisms and some measures to minimize dendrite formation were presented.